2019
DOI: 10.1055/s-0039-1697592
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Patient-Facing Visualizations of Personal Health Data

Abstract: Objectives As personal health data are being returned to patients with increasing frequency and volume, visualizations are garnering excitement for their potential to facilitate patient interpretation. Evaluating these visualizations is important to ensure that patients are able to understand and, when appropriate, act upon health data in a safe and effective manner. The objective of this systematic review was to review and evaluate the state of the science of patient-facing visualizations of personal health d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 72 publications
1
34
0
Order By: Relevance
“…32 Portals may increase patient understanding of the care plan 33 ; yet ways to visualize such data provided in portals needs further work to result in more meaningful use. 34 Concerns about data management (security, privacy, and reliability of data), which was a key issue in the 2013 study, 20 was not identified as a major barrier in our study. In fact, there may be a larger need for a single accurate record that travels with the patient in rural areas, as illustrated by problems in information exchange between surgeons and primary care providers.…”
Section: Comparison With the Literaturementioning
confidence: 66%
“…32 Portals may increase patient understanding of the care plan 33 ; yet ways to visualize such data provided in portals needs further work to result in more meaningful use. 34 Concerns about data management (security, privacy, and reliability of data), which was a key issue in the 2013 study, 20 was not identified as a major barrier in our study. In fact, there may be a larger need for a single accurate record that travels with the patient in rural areas, as illustrated by problems in information exchange between surgeons and primary care providers.…”
Section: Comparison With the Literaturementioning
confidence: 66%
“…The data generated by the platform should be considered of value to users if it is readable, easily interpreted, and personalized. 46 The point is to make the data understandable, favor graphics and visualizations that are simple and customizable, by allowing users to filter the data according to their needs. The issue of data visualization is therefore an issue that should not be overlooked, especially in the design of technologies aimed at supporting self-care practices.…”
Section: Discussionmentioning
confidence: 99%
“…To get the most out of viewing their test results on patient portals, patients need to understand (1) what the test is for, (2) how to interpret the test, and (3) what to do in response. 40,41 Further research is needed to directly assess the impact of different data displays and user interface designs on patients' ability to achieve this level of understanding. 41 Second, among patients with diabetes, limited health literacy is typically associated with worse health outcomes and can be a barrier to patient portal use.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Further research is needed to directly assess the impact of different data displays and user interface designs on patients' ability to achieve this level of understanding. 41 Second, among patients with diabetes, limited health literacy is typically associated with worse health outcomes and can be a barrier to patient portal use. 9,42 Tieu et al have shown that despite expressing enthusiasm for patient portal use, patient portal users with limited health literacy struggle with medical terminology and a lack of literary level-appropriate health information.…”
Section: Discussionmentioning
confidence: 99%